Tumor-promoting macrophages prevail in malignant ascites of advanced gastric cancer - Eum, Hye Hyeon; Kwon, Minsuk; Ryu, Daeun; Jo, Areum; Chung, Woosung; Kim, Nayoung; Hong, Yourae; Son, Dae-Soon; Kim, Seung Tae; Lee, Jeeyun; Lee, Hae-Ock; Park, Woong-Yang (Experimental & molecular medicine, 2020)
Gastric cancer (GC) patients develop malignant ascites as the disease progresses owing to peritoneal metastasis. GC patients with malignant ascites have a rapidly deteriorating clinical course with short survival following the onset of malignant ascites. Better optimized treatment strategies for this subset of patients are needed. To define the cellular characteristics of malignant ascites of GC, we used single-cell RNA sequencing to characterize tumor cells and tumor-associated macrophages (TAMs) from four samples of malignant ascites and one sample of cerebrospinal fluid. Reference transcriptomes for M1 and M2 macrophages were generated by in vitro differentiation of healthy blood-derived monocytes and applied to assess the inflammatory properties of TAMs. We analyzed 180 cells, including tumor cells, macrophages, and mesothelial cells. Dynamic exchange of tumor-promoting signals, including the CCL3–CCR1 or IL1B–IL1R2 interactions, suggests macrophage recruitment and anti-inflammatory tuning by tumor cells. By comparing these data with reference transcriptomes for M1-type and M2-type macrophages, we found noninflammatory characteristics in macrophages recovered from the malignant ascites of GC. Using public datasets, we demonstrated that the single-cell transcriptome-driven M2-specific signature was associated with poor prognosis in GC. Our data indicate that the anti-inflammatory characteristics of TAMs are controlled by tumor cells and present implications for treatment strategies for GC patients in which combination treatment targeting cancer cells and macrophages may have a reciprocal synergistic effect. Gastric cancer: Understanding cellular interactions suggests potential treatments New strategies for treating advanced gastric cancer could emerge from insights into the interactions between white blood cells called macrophages and tumor cells in fluid known as malignant ascites that accumulates in the abdomen. Researchers in Seoul, South Korea, led by Hae-Ock Lee at The Catholic University of Korea and Woong-Yang Park at the Samsung Medical Center compared macrophages from healthy subjects with those from gastric cancer ascites. They identified molecular signaling interactions between tumor cells and macrophages that recruited macrophages into the ascites and converted them into more anti-inflammatory forms. The macrophages were then able to promote the activities of the cancer cells. The results suggest that chemicals able to inhibit or deplete proteins now identified as involved in controlling these synergistic interactions could become a new class of therapeutic agents.